PWA-EU: extending the PWA approach for promoting End-User Empowerment - De Andrade Cardieri, Giulia (2019)
Progressive Web App (PWA) is a new approach to the development of mobile applications (apps) which was proposed by Google in 2015. It combines technology resources of both web and native apps. Meta-design is an End-User Development (EUD) approach from which end-users participate actively of a system’s design process. Yet PWAs are a recent technology and the impacts of associating EUD and PWAs has been little explored. In this research, we present an investigation about end-users interactions when they act as codesigners on PWA apps. As the traditional PWA approach is limited regarding users acting as co-designers, we propose the PWA-EU approach, an extension of the traditional PWA architecture that includes meta-design concepts. We evaluated our approach concerning both end-users and developers perspectives. With regards to the end-users, we built a mobile app based on the PWA-EU approach and conducted a study in which a group of participants acted as co-designers of the app, and another group with participants interacting as non-designers. On the study with developers, we grouped 23 participants according to their professional background. Moreover, each developer had to implement the three architectural parts from the PWA-EU proposal and one from the traditional PWA approach. The findings suggested PWA-EU is a useful architecture for developers with some experience and for end-user empowerment on mobile apps, which brought significant contributions to the PWA and EUD fields.